Nordic countries’ practices of state regulation of immigrant integration - Vladyslav Butenko; Aleksei Igorevich Chekmazov (RUDN Journal of Public Administration)
The effectiveness of immigrant integration policies remains a topical issue in academic literature and political practices. This issue touches upon aspects of finding a balance between ensuring a high level of social guarantees for immigrants, on the one hand, and the economic stability of welfare states, on the other. The impetus was given by the 2015-2016 migration crisis, which demonstrated the inability of the European Union to promptly develop appropriate management strategies for the reception, accommodation, and integration of new arrivals. The aim of this study is to analyze the models and approaches to immigrant integration. Using comparative methodology, the authors argue that traditional models of assimilation and multiculturalism have lost their relevance and have been replaced by the model of civic integration as a response to the challenges faced by the Nordic countries as a result of the migration crisis. Adaptation to modern problems associated with the intensification of migration flows to the Nordic countries marks a “civic turn” in immigrant integration policies. The conducted analysis of state regulation in the field of immigrant integration in Denmark, I celand, Norway, Finland, and Sweden shows common trends, determined primarily by the logic of economic expediency. This allows the authors to conclude that immigrant integration policies are converging, which qualitatively distinguishes the current state of affairs from the period from the 1970s to the migration crisis, when the policies of the Northern European countries were characterized by multidirectionality.